Effect of Combination of Poultry Manure and Rice Husk Biochar on Soil Fertility and Rice Plants - Edy Syafril Hayat; Sri Andayani; Rita Hayati (International Journal of Multi Discipline Science, 2023)
Rice plants occupy a strategic position as a staple food producer for the people of Indonesia. Faced with limited suboptimal soil fertility, especially low levels of nutrients and soil pH, the use of organic fertilizers combined with local ameliorants is one solution to increase soil fertility. The purpose of this study was to obtain a combination of chicken or quail manure with rice husk biochar, which can reduce the use of inorganic fertilizers (urea, SP-36, and KCl). This study used a completely randomized design (CRD) consisting of 7 treatments (A, B, C, D, E, F, and G) which was a combination of 100% to 25% inorganic fertilizer of the recommendations, chicken manure or bird manure quail 5 tons/ha, and rice husk biochar 5 tons/ha. The parameters observed were plant height, total chlorophyll, seed dry weight, soil pH, soil NPK content, and Al-dd content. Observational data were analyzed with the F test at the 5% level then further tests were carried out using the Honest Significant Difference (HSD) test. The results showed that the treatments had a very significant effect, namely C, D, and E treatments resulted in a decrease in Al-dd, and an increase in K and had a significant effect on rice plant height. It was concluded that a combination of 5 tons/ha of chicken manure or quail manure with 5 tons/ha of biochar could increase soil fertility and rice plant height during the vegetative period and could substitute inorganic fertilizers up to 50% of the recommended dose.